Protoplasts: From Isolation to CRISPR/Cas Genome Editing Application - Yue, Jin-Jun; Yuan, Jin-Ling; Wu, Fu-Hui; Yuan, Yu-Hsuan; Cheng, Qiao-Wei; Hsu, Chen-Tran; Lin, Choun-Sea (Frontiers in Genome Editing, 2021)
In the clustered regulatory interspaced short palindromic repeats (CRISPR)/CRISPR associated protein (Cas) system, protoplasts are not only useful for rapidly validating the mutagenesis efficiency of various RNA-guided endonucleases, promoters, sgRNA designs, or Cas proteins, but can also be a platform for DNA-free gene editing. To date, the latter approach has been applied to numerous crops, particularly those with complex genomes, a long juvenile period, a tendency for heterosis, and/or self-incompatibility. Protoplast regeneration is thus a key step in DNA-free gene editing. In this report, we review the history and some future prospects for protoplast technology, including protoplast transfection, transformation, fusion, regeneration, and current protoplast applications in CRISPR/Cas-based breeding.